Investigation on how pre-service elementary mathematics teachers write and use mathematical definitions - Özyıldırım-Gümüş, Feride; Şahiner, Yeter (International Electronic Journal of Elementary Education, 2017)
The aim of the study was to determine whether pre-service elementary mathematics teachers could write and use mathematical definitions. For this reason, the question sheet containing two questions, was given to 76 pre-service teachers in a public university who was taking general mathematics course. Qualitative research method was used during data analysing. According to the answers given by them, five themes for the first and six themes for the second question were classified. In order to reach detailed results, semi- structured interviews were conducted with one pre-service teacher for each theme. Findings showed that they had difficulties in writing a formal definition assumed to be known and in using a given definition assumed to be not known of a mathematical concept.